Urinalysis as a diagnostic tool for febrile urinary tract infection in children aged 2 months - 2 years - Ayijati Khairina; Partini Pudjiastuti Trihono; Zakiudin Munasir (Paediatrica Indonesiana, 2014)
Background Children aged 2 months to 2 years with febrileurinary tract infection (UTI) need special attention consideringkidney complications, unspecified symptoms, and difficult urinesample collection. Urinalysis was the main supportive examinationfor UTI because of its immediate result and widespreadavailability.Objective To estimate urine nitrite, leukocyte esterase (LE),leucocyturia, bacteriuria, and their combinations as a diagnostictool for febrile UTI in children aged 2 months to 2 years.Methods This is a diagnostic study held in Cipto MangunkusumoHospital, Tangerang General Hospital, Fatmawati Hospital, andBudhi Asih Hospital, involving 7 5 children aged 2 months to 2years. Urine samples for urinalysis and urine culture were collectedusing urine collector in all subjects. Clinical pathologists whoperformed urine culture, did not know the results of urinalysis.Results By parallel test analyses, we found that the best diagnosticvalue was the combination of 3 tests (LE, leucocyturia, andbacteriuria). This combination test showed sensitivity, specificity,positive predictive value (PPV), negative predictive value (NPV),positive likelihood ratio (LR+), and negative likelihood ratio(LR-) of 69%, 95%, 85%, 88%, 13.1, and 0.3.Conclusion The combination test of LE, leucocyturia, andbacteriuria shows high specificity, NPV, and LR+ . Therefore, thenegative results of these 3 tests in combination can be used to ruleout UTI.